Associations Between Life-Course Socioeconomic Conditions and the Pace of Aging. Issue 11 (24th December 2021) - Schrempft, Stephanie; Belsky, Daniel W; Draganski, Bogdan; Kliegel, Matthias; Vollenweider, Peter; Marques-Vidal, Pedro; Preisig, Martin; Stringhini, Silvia
Abstract: Background: Socioeconomic disadvantage is a well-established predictor of morbidity and mortality, and is thought to accelerate the aging process. This study examined associations between life-course socioeconomic conditions and the Pace of Aging, a longitudinal measure of age-related physiological decline. Methods: Data were drawn from a Swiss population-based cohort of individuals originally recruited between 2003 and 2006, and followed up for 11 years (2 834 women, 2 475 men aged 35–75 years [mean 52]). Pace of Aging was measured using 3 repeated assessments of 12 biomarkers reflecting multiple body systems. Analysis tested associations of socioeconomic conditions with physiological status at baseline and with the Pace of Aging. Results: Participants with more life-course socioeconomic disadvantage were physiologically older at baseline and experienced faster Pace of Aging. Effect sizes (β) for associations of childhood socioeconomic disadvantage with baseline physiological status ranged from 0.1 to 0.2; for adulthood socioeconomic disadvantage, effect sizes ranged from 0.2 to 0.3. Effect sizes were smaller for associations with the Pace of Aging (<0.05 for childhood disadvantage, 0.05–0.1 for adulthood disadvantage). Those who experienced disadvantaged socioeconomic conditions from childhood to adulthood aged 10% faster over the 11 years of follow-up as compared with those who experienced consistently advantaged socioeconomic conditions. Covariate adjustment for health behaviors attenuated associations, but most remained statistically significant. Conclusions: Socioeconomic inequalities contribute to a faster Pace of Aging, partly through differences in health behaviors. Intervention to slow aging in at-risk individuals is needed by midlife, before etiology of aging-related diseases become established.